(untitled) (CIPEEX, 2026)
INTRODUCTION: Aging is associated with several physiological and pathological changes that increase the risk of falls in older adults. These falls, in turn, significantly impact the quality of life of the elderly. OBJECTIVE: To analyze the association between quality of life and risk of falls in older adults. METHODS: This is an observational, analytical, cross-sectional study in which 84 older adults of both sexes, aged 60 years and over, enrolled in the Open University for Older Adults (UniAPI), were evaluated. The Timed Up and Go test, the Downton Fall Risk Index, and the World Health Organization Quality of Life Assessment (WHOQOL) were used to analyze the risk of falls and quality of life of these older adults. Statistical analysis was performed using the Chi-square test, with a significance level of p<0.05. RESULTS: The study showed a predominance of younger older adults (60–74 years), mostly with few comorbidities and low risk of falls. When associating the Downton Scale with WHOQOL, it was revealed that worse quality of life, especially in the physical, psychological, and environmental domains, was associated with a higher risk of falls. CONCLUSION: Older adults with poorer self-perception of quality of life, particularly in the physical, psychological, and environmental domains, presented a higher risk of falls.